0198 Delivering pre-hospital emergency medicine simulation-based medical education: A pilot of a student-led multidisciplinary teaching team. (2nd November 2015) - Gopal, Alan; Taylor, Kathryn; Harlinska, Anna; Smith, Alex; Cartledge, Ian; Ferguson, Roger; Wong, Abilius
Abstract : Background: The Hull York Medical School Pre-hospital Care Programme (HYMS PCP) 1 exposes and develops medical students in pre-hospital care (PHC) through academic and clinical education. For the purpose of the latter, students are trained, accredited and gain experience as first-responders in Yorkshire Ambulance Service Community First Responders (YAS CFR) 2 and Lincolnshire Integrated Voluntary Emergency Service (LIVES). 3 To support expansion of student responder units and in response to student feedback requesting more formal teaching opportunities, HYMS-PCP Responder Development Days (HRDDs) were created. Methodology: A pilot of 4 HRDDs were designed to aid academic and clinical development of students in PHC. Using the GMC approved Pre-hospital Emergency Medicine Curriculum, 4 a student orientated academic curriculum was created to focus the HRDDs. Each HRDD was designed around a medical emergency theme (e.g. cardiac) and was comprised of paramedic-facilitated simulations. These were preceded by student and paramedic delivered lectures and case presentations to enforce a consultant-approved level of understanding surrounding the topic, authorising near-peer teaching in a safe and responsible manner. Qualitative and quantitative feedback was encouraged from participants and teaching team. Results: 4 HRDDs were organised successfully, with 56 attendees and an average satisfaction rating of 8.8/10 (1 very dissatisfied, 10 maximum satisfaction). All who completed the questionnaire indicated they found the session helpful (100%) and felt increased confidence in performing their first response duties (100%). Qualitative feedback was also positive. Conclusion: Our results strongly suggest the pilot was beneficial on both sides of the teaching partnership. Our pilot developed the team in multidisciplinary teamwork and professionalism in addition to providing safe and effective 5 education. In terms of creating and managing the project, entrepreneur-based education is proven to have a positive effect on personal development. 6 We intend to re-commence and expand the HRDDs as a permanent part of the programme. References: Wong A, Pham K, Preece J. Poster session presented at: BASICS conference; 2013 Oct 11–12; Dudley, West Midlands, UK Community First Responders Yorkshire Ambulance Service. Yorkshire Ambulance Service NHS Trust, United Kingdom; [cited 2015 Aug 4]. Available from: http://www.communityresponders.yas.nhs.uk/ LIVES. LIVES Responders. LIVES.org.uk. [cited 2015 Aug 4]. Available from: http://www.lives.org.uk/about-us/responders/ IBTPHEM. Sub-specialty training in pre-hospital emergency medicine. Version 4. 20 Feb 2012. Available from: www.ibtphem.org.uk/IBTPHEM/Resources.html McGaghie WC, Siddall VJ, Mazmanian PE, et al . Chest 2009;135 (3 Suppl): 62S–68S Moberg KS. SSRN Electron. J. [Internet]. 2012 Jul 1 [cited 2015 Aug 4]; Available from: http://papers.ssrn.com/abstract=214762